2014
DOI: 10.3168/jds.2013-7092
|View full text |Cite
|
Sign up to set email alerts
|

Study of the chemical composition, proteolysis, volatile compounds, and textural properties of industrial and traditional Beaten (Bieno sirenje) ewe milk cheese

Abstract: The objective of this study was to determine the gross composition, proteolysis, and volatile and texture profiles during ripening of industrial (IND) and traditional (TRD) Beaten (Bieno sirenje) cheeses made by using ewe milk. In the course of the analyses, statistical differences were determined in some physicochemical parameters, nitrogen fractions, and total free amino acid levels between TRD and IND types of cheese. Higher levels of proteolysis were observed in IND cheeses than in TRD cheeses during ripen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 43 publications
1
9
0
13
Order By: Relevance
“…It has been reported that high proteolytic activity in fermented dairy products, delivers a greater production of volatile compounds [29], thus, in this study proteolytic activity of two wild L. lactis strains was determined in the fermented milks. Fermented milk with both strains (co-FM) presented significantly (p < 0.05) higher proteolytic activity (131.53 ± 32.04 µg/mL L-leucine) than FM-572 (37.64 ± 1.06 µg/mL L-leucine), FM-571 (23.81 ± 0.67 µg/mL L-leucine), or unfermented milk (17.56 ± 0.64 µg/mL L-leucine).…”
Section: Milk Proteolysis and Free Amino Acid Determinationmentioning
confidence: 99%
“…It has been reported that high proteolytic activity in fermented dairy products, delivers a greater production of volatile compounds [29], thus, in this study proteolytic activity of two wild L. lactis strains was determined in the fermented milks. Fermented milk with both strains (co-FM) presented significantly (p < 0.05) higher proteolytic activity (131.53 ± 32.04 µg/mL L-leucine) than FM-572 (37.64 ± 1.06 µg/mL L-leucine), FM-571 (23.81 ± 0.67 µg/mL L-leucine), or unfermented milk (17.56 ± 0.64 µg/mL L-leucine).…”
Section: Milk Proteolysis and Free Amino Acid Determinationmentioning
confidence: 99%
“…The amount of WSN and 12% TCA‐SN in cheese made from raw or pasteurized milk with a starter culture, respectively, is lower than those reported for different varieties of white brined cheeses by other researchers (Goncu & Alpkent, 2005; Maćej, Dozet, & Jovanović, 2006; Moatsou, Massouras, Kandarikis, & Anifantakis, 2002; Sarić, Lüthi‐Pengt, & Puhan, 2002). This shows that heat treatment used during the manufacture of the cheese and the moisture content has a principal impact on the level of retained rennet in the curds (Sulejmani, Hayaloglu, et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…They are specified by intensive proteolysis during which a great number of low molecular‐weight peptides are formed (Barać, Pešić, Vučić, Vasić, & Smiljanić, 2017; Radulović et al., 2011). Beaten “Bieno Sirenje” is a brined cheese that is a very popular variety in Macedonia with the consumption of about 50%–70% of total cheese consumption (Sulejmani, Hayaloglu, & Rafajlovska, 2014). The cooking procedure is a crucial step in Beaten cheese manufacture and substantially affects the physical, biochemical, and sensory properties of the cheese.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulejmani et al [26] found 73 volatile compounds, including alcohols (16), esters (17), acids (14), terpenes (7), ketones (5) and aldehydes (4) during the 180-day period of traditional Beaten (Bieno sirenje) cheeses.…”
Section: çEti̇nkayamentioning
confidence: 99%